Comparison of ball-and- racket impact force in two-handed backhand between different directions of stroke - Hsu, C.; Lo, K.; Peng, Y.; Wang, L. (ISBS - Conference Proceedings Archive (Konstanz), 2009)
Modern rackets have facilitated a modification in playing style from one of technique to one characterized by power (Miller, 2006). The aim of this report is compare the impact force and moment of upper extremity joint between the advanced and the intermediate group during two-handed stroke in across-court and down-the-line. Based on a few studies in backhand stroke, especially the two-handed backhand with different direction, this study is essential for understanding stroke characteristics.